Pengaruh Keterlibatan Orang Tua dan Teknologi terhadap Nilai IPK Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Siburian, Marshanda; Perangin-Angin, Emia; Lizu Sitanggang, Twin; Lumban Batu, Siska; Taufiq Umar, Andi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to identify the influence of parental involvement and technology on student GPA scores at the Faculty of Economics, Universitas Negeri Medan. This research uses quantitative methods with a descriptive approach and hypothesis testing. Data collection was carried out by distributing questionnaires or Likert scales via Google Form. Data analysis uses multiple linear regression. The research results show that (1) parental involvement has a partial and significant influence on increasing student GPA with a tcount value of 4,859 which is greater than ttable 2,024, (2) technology involvement hasnt influence on increasing student GPA with a tcount value of 0.388 which greater than ttable 2,024, (3) parental involvement and technology together have a significant positive influence on increasing student GPA with a calculated Fvalue of 19,232 which is greater than Ftable 3,25. Based on these results, it can be concluded that parental involvement and technology influence the increase in GPA of students at the Faculty of Economics, Universitas Negeri Medan